Neurotherapeutics across blood–brain barrier: screening of BBB-permeable and CNS-active molecules for neurodegenerative disease - Mohan Kumar, D.; Talwar, Priti (Frontiers in Pharmacology, 2025)
Neurotherapeutics that are effective in the central nervous system (CNS) of the brain require an accurate estimation of their uptake across the blood–brain barrier (BBB), a highly selective membrane between the bloodstream and the nervous system that restricts and regulates the entry of small molecules. Drugs that influence the CNS must permeate the BBB prior to reaching their target site. Therefore, the prediction of BBB permeability with CNS activity is a fundamental aim and significant research objective in neuropharmacology. Here, we utilized in silico approaches and available machine learning models ranging from physicochemical properties to structure–activity relationships in a CNS drug discovery pipeline to identify BBB-permeable molecules. These models pertain to pharmacophore-based virtual screening, BBB permeability and CNS activity prediction, medicinal chemistry, ADME, toxicity profiling, drug-likeness, side effect resources, and bioactivity studies. A total of 2,127 active small molecules were initially screened based on the structure similarity of five FDA-approved drugs of particular interest for neurodegenerative diseases. Based on the BBB model, they were classified into 582 BBB permeable and 1545 BBB non-permeable molecules. Most of the BBB-permeable molecules were reported to have direct CNS activity due to their high brain-to-blood ratio. Finally, 112 active CNS molecules were prioritized based on pharmacokinetics, toxicophores, and drug-likeness. Additionally, the neuroactivity toward the CNS of small molecules was predicted to be a nootropic, neurotrophic factor enhancer, and neuroinflammatory modulator. Thus, by ensuring their impact on BBB integrity and the neuroprotective properties of small molecules, they can in future be transformed into food supplements and nutraceuticals that could provide valuable insights into neurotherapeutics as promising therapeutic interventions for neurodegenerative diseases.